PERFORMA SYARAT PENDIDIKAN PENYIDIK DAN IMPLIKASINYA TERHADAP PROFESIONALITAS PENYIDIK POLRI DALAM PENANGANAN PERKARA: (Studi Manajemen Sumber Daya Manusia di Perguruan Tinggi Ilmu Kepolisian) - Herman Sopian; Bambang Wijaya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
The unprofessionality of police personnel in a case handling often occurs in the course of the legal world in Indonesia. Violence is often perpetrated by police in the investigation to obtain a suspect's acknowledgment. From the various studies that have been there, many factors cause the police not to act professionally while carrying out its function as an investigator to reveal a legal case. These factors include low education and recruitment processes that do not run transparently as regulated in the applicable regulations. So there needs to be a strong commitment from the police leadership in the development of police human resources through the improvement of education and to carry out the correct and strict police officer recruitment procedures.